Histrionic Personalities in the Everyday Life and in Power: An Approach towards Interaction an Psychological Characteristics - Reshetnikov Mikhail (Selected Topics in Humanities and Social Sciences Vol. 8, 2021)
In this paper, most prominent psychological characteristics of histrionic personalities, specifics of their behaviour and thinking in case of social normality are outlined. Histrionic personalities, like all other people, strive for others’ respect, for financial success and social recognition. The paper specifically focuses on histrionic personality with leadership qualities striving for power. Psychological defence mechanisms, excessive use of repression, typical motivations, self-esteem and aspirations of histrionic personalities are described as well as characteristics of their conscience, memory and behaviour in situations of intrapsychic and interpersonal conflicts. The author suggests the most reasonable ways of interaction with this type of accentuated personalities in psychotherapy and in everyday life.